Multiple Sclerosis: A Systematic Review of a Neurological Disorder - Apeksha Pandey (International Journal of Genetic Modifications and Recombinations, 2023)
The inflammatory illness known as multiple sclerosis (MS) is brought on by outside influences that affect a biologically vulnerable host. It has 3 separate diagnostic phases: the pre-clinical phase, which can only be discovered by MRI; the relapsing-remitting (RRMS) phase, which again is defined by bouts of neurological malfunction accompanied by remission; and the progressing phase, which often develops from either the relapse phase. Unfortunately, the majority of relapse MS medications are ineffective against progressing illness. A compartmentalised inflammatory response comprising neurons and glial in the nervous system, in addition to completely impervious mechanisms that cause neuronal damage, are characteristics of progressing MS. Identifying the processes of tumor growth, creating treatments for progressing MS, and establishing the extent towards which progressing illness may be avoided by techniques that help are significant issues for MS study. This whole review covers about the, types and variants, pathophysiology, causes, diagnosis, therapies, biomarkers, cells involved and management of the disease.
Keywords: Relapsing-remitting; pathophysiology; progressing MS; tumor growth